Development and validation of a system of systems (SoS) evaluation framework : the case of Singapore’s container port development - Huang, Wei Qiang. (2009)
In today’s world, problems are facing decision-makers within government and industry and the key characteristic of these problems is associated with the subject on system of systems (SoS). For a sustainable economic development, the government and industry must continually fund and develop large scale infrastructure. The challenge is to make key decisions and execute them in an ever competitive time frame to support and prosper in the economic activities. The objective of this project is to go beyond a traditional large scale infrastructure management perspective to tackle the issue using system of systems (SoS) approach. It is presented in three phases of proposition, reasoning and evidence on the use of SoS approach in large scale infrastructure project. From a systematic approach to study such portfolio, the study would subsequently identify key lessons learned that other developing countries/cities may find useful. The focus of the proposition phase will be on reviewing and synthesizing cited references on the definitions and characteristics of SoS. Various characteristics of a typical SoS are listed with details studied both independently and in relationship. A SoS framework is subsequently constructed to act as a reference model for infrastructural projects. Special attention is paid on approaching systematic thinking at basic level on how to address the SoS challenges. The reasoning phase further qualifies the proposition and the validation of the framework, with Singapore’s world class port operator PSA adopted as a reference. It proves a clear existence of SoS environment in the development of large scale infrastructure is a vital factor for success. The characteristics of SoS and its relevance to large scale infrastructure development are covered. The emphasis of the study is on the value of SoS concept by identifying important aspect such as critical success factors and best practices and set them as a learning model for other developing ports. In the evidence phase, facts, figures and various performance indicators are being put together to support the theory of system of systems in large scale infrastructure development. These evidence acts as a strong pillar of support for a ‘model infrastructure’ for governments and port planners to adopt a ‘planned SoS’ structure. By taking a SoS perspective and approach, factors such as infrastructural economy, national development, resource allocation, expandability and incremental development will be well covered.